The role of voluntary commitments in realizing the promise of the Blue Economy. (November 2021) - Voyer, Michelle; Allison, Edward H.; Farmery, Anna; Fabinyi, Michael; Steenbergen, Dirk J.; van Putten, Ingrid; Song, Andrew M.; Ogier, Emily; Benzaken, Dominique; Andrew, Neil
Highlights: Voluntary commitments play an important role in oceans governance. The Blue Economy is a rapidly evolving and under-governed space. Commitments to high level meetings reveal trends and gaps in Blue Economy governance. Small Islands States are well represented but some major maritime states are not. Commitments focus on growing capacity and new industries and shrinking fisheries. Abstract: Voluntary (or non-binding) commitments offer an action-oriented mechanism for addressing interconnected, complex and pressing issues. Though not designed to replace negotiated or binding outcomes, voluntary commitments can offer a critical tool in currently ungoverned or under-governed systems. The Blue Economy is an example of a rapidly evolving agenda where formal governance arrangements are at best nascent, in part due to the trans -border nature of issues and prominent involvement of multiple types of actors. As such voluntary commitments provide an important mechanism through which to monitor the evolution of the concept and identify gaps or shortfalls in its implementation. Our analysis of global voluntary commitments on the Blue Economy made to recent high-profile ocean futures meetings, found a trend towards capacity development, research, and investment in emerging and larger scale sectors such as offshore aquaculture and renewable energy. A concurrent focus was on securitizing, regulating or diverting effort from historically significant fisheries sectors. European organizations are playing a dominant role in Blue Economy commitments, with a notable absence of commitments from major Blue Economy powers such as China and India. We identify a number of gaps and shortfalls, particularly in relation to active consideration of social equity in the Blue Economy. We identify a range of recommendations on how these deficiencies may be addressed through a greater focus on a broader suite of objectives and a more inclusive approach to ocean meetings.